SIFAT FISIK KIMIA DAN ORGANOLEPTIK JELLY PADA BERBAGAI RASIO GULA PASIR-DAGING BUAH NAGA (Hylocereus polyrhizus Britt and Rose) - wulandari, Sri; kadekoh, Indrianto; alam, Nur (AGROTEKBIS, 2018)
This study aims to determine the effect of the ratio of juice fruit dragon - sugar on the physical properties of chemical and organoleptic jelly and to get the ratio of juice dragon - sugar were giving out the best impact on the physical, chemical and organoleptic jelly and to determine levels of Anthocyanins and vitamin C dragon fruit before and after process into jelly. The research was conducted from March to May 2017 in the Laboratory of Agro-Industry Faculty of Agriculture, Tadulako University. This study used a completely randomized design (CRD) 1 factor. Factor is the ratio of sugar - juice dragon comprising 7 levels a ratio of 110 g of dragon fruit : 50 g sugar, 100 g of fruit juice dragon : 60 g sugar, 90 g dragon fruit : 70 g sugar, 80 g dragon fruit juice : 80 g sugar, 70 g ratio dragon fruit juice : 90 g sugar, 60 g ratio dragon fruit juice : 100 g sugar, 50 g and the ratio of dragon fruit juice : 110 g sugar. The research results on softness, the degree of clarity, total soluble solid, the lowest score of aroma, color, hardness and taste, but had higherst levels of anthocyanins and vitamin C. Flavor jelly was highest in the treatment of dragon fruit juice 80 g : 80 g sugar. Treatment of 80 g of dragon fruit juice : 80 g sugar gave a better effect on the characteristics of the dragon fruit juice jelly. Levels of anthocyanins and vitamin C of fresh dragon fruit decreased after made into jelly. Anthocyanins levels were reduced by 69.33 to 82.44% and Vitamin C from 59.89 to 86.58%.